Pengaruh Model Problem Based Learning (PBL) Terhadap Hasil Belajar Tematik Pada Siswa Kelas IV SD GMIM I Kakaskasen - Mangangantung, Jeanne M.; Kamasaan, Asmaul Husna U.; Rorimpandey, Widdy H. F. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the effect of the Problem Based Learning (PBL) learning model on student learning outcomes in thematic learning with energy material and its uses. The findings using the T test and the Liliefors analysis technique show. The student learning outcomes with conventional learning, the posttest score in the control class was 66.09. Meanwhile, the learning outcomes using the Problem Based Learning (PBL) model in the experimental class, the posttest score was 89.61. There is a significant influence with the Problem Based Learning learning model on student learning outcomes in thematic learning. This is in accordance with the t test calculation, the figure obtained is 4.163 while the t table is 1.680, so it is proven that there is a significant influence with the Problem Based Learning (PBL) model. The conclusion in this research states that the average learning outcomes of students taught using the Problem Based Learning (PBL) learning model are better than the average learning outcomes of students taught using conventional learning.